Right ventricular mobile thrombus in end-stage hypertrophic cardiomyopathy. Issue 5 (May 2017) - Kusume, Takahiro; Kubokawa, Shoichi; Kaname, Noriyoshi; Nakaoka, Yoko; Kotani, Toshiaki; Imai, Ryuichiro; Nishida, Koji; Seki, Shuichi; Kawai, Kazuya; Hamashige, Naohisa; Doi, Yoshinori
Abstract: We report the first case of a mobile right ventricular apical thrombus in hypertrophic cardiomyopathy in the absence of right ventricular apical aneurysm. An 87-year-old man who had been diagnosed as having hypertrophic cardiomyopathy presented with gross peripheral edema and exertional dyspnea. He had been on warfarin, β-blockade, and diuretics. Electrocardiograms indicated progression of the disease with atrial fibrillation, low voltage and prominent Q waves in the left precordial leads. Echocardiograms revealed ventricular septal and apical hypertrophy, hypokinetic distal left ventricle, and dilated and severely hypokinetic right ventricle. A mobile thrombus (18 mm × 18 mm) was detected in the right ventricular apex. Cardiac computed tomography and magnetic resonance imaging confirmed a large thrombus in the right ventricular apex. Late gadolinium enhancement was present in the interventricular septum and distal segments of both ventricles, indicating myocardial fibrosis and scar. A dilated and poorly contracting right ventricle, particularly right ventricular apex, in end-stage hypertrophic cardiomyopathy, associated with stagnant blood flow in the apex, was hypothesized as being responsible for right ventricular apical thrombus formation in the absence of right ventricular aneurysm. <Learning objective: This is the first report of a mobile thrombus in the right ventricle in hypertrophic cardiomyopathy. Since mobile right ventricular thrombi may cause life-threatening pulmonary embolism, and detection of thrombi in the right ventricular apex may be difficult by echocardiographic examination, we suggest the use of cardiac computed tomography and/or magnetic resonance imaging that are useful tools to detect right ventricular apical thrombi when severe right ventricular dysfunction is suspected in end-stage hypertrophic cardiomyopathy.>